2019
DOI: 10.32598/jccnc.5.3.141
|View full text |Cite
|
Sign up to set email alerts
|

Professional Image Perceptions in First-year Nursing Students

Abstract: Background: Determining the professional image perceptions of the first-year nursing students who have recently chosen the nursing profession is of great importance in delineating the profession profile. The present study aimed to determine the image perception of first-year nursing students and its related factors.Methods: This descriptive cross-sectional research was conducted in the Fall semester of the 2019-2020 academic year. In total, 105 first-year nursing students were selected from the Nursing Departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Many factors-such as school curriculum, educators, clinical practice environment, mentor nurses, and peers-contribute to the professional development of nursing students (Safadi et al, 2011). To develop a more positive professional image among students, it is recommended that academic and clinical nurses serve as role models and guides (Yılmaz, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many factors-such as school curriculum, educators, clinical practice environment, mentor nurses, and peers-contribute to the professional development of nursing students (Safadi et al, 2011). To develop a more positive professional image among students, it is recommended that academic and clinical nurses serve as role models and guides (Yılmaz, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a strong and positive professional image among nursing students is important for their professional development and commitment (Dost & Bahçecik, 2015). Nursing image has always been considered an important concept in nursing (Kartal & Kantek, 2018) and there are studies in the literature that define the nursing image and influencing factors of students (Elibol & Harmancı Seren, 2017; Kim & Kwon, 2018; Yılmaz, 2019). In the studies, the students' perceptions of nursing image showed low (Elibol & Harmancı Seren, 2017) or above average in other words positive (Kim & Kwon, 2018; Yılmaz, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies claim that the public image of nurses is perceived negatively [ 16 , 17 ]. In contrast, a favorable perception of nurses was observed [ 18 ]; however, few studies have highlighted the positive perception of nurses’ public image, status, and power as a profession during the COVID-19 pandemic [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the image of nursing has always been of great importance and concern. Corresponding to the literature, nursing students' perceptions of the image of nursing are affected by the perspective of society towards the profession [5].…”
Section: Introductionmentioning
confidence: 99%